Synthesis of plasmonic Au–CuS hybrid nanocrystals for photothermal transduction and chemical transformations. Issue 31 (10th March 2016) - Sun, Chao; Liu, Mengya; Zou, Yu; Wei, Jiandong; Jiang, Jiang
Abstract : Plasmonic Au–CuS heterodimers were prepared by tuning Cu–S reactivity, which shows synergistically enhanced optical absorption and can be further chemically transformed to hybrids like Au–CuInS2 and Au–Cu2 ZnSnS4 . Abstract : Plasmonic Au–copper sulfides hybrid nanocrystals are of great interest for both fundamental research and application in optoelectronics, catalysis, and biomedicine, in which a precise and high-yield synthesis of the hybrid nanocrystals is required. Herein, we investigated colloidal synthesis of Au–CuS hybrid nanocrystals based on a seed-mediated method. Different from previously reported deposition of Cu-rich Cu chalcogenides, we found that decreasing the Cu–S reaction rate is critical for the deposition of relatively S-rich CuS on Au seeds in high yield, which can be achieved by using a chlorobenzene solution containing a small amount of oleylamine as the solvent. The influence of the S/Cu feed molar ratio and reaction temperature on the formation of Au–CuS hybrid nanocrystals has also been investigated. The obtained Au–CuS hybrids showed better photothermal transduction efficiency over CuS nanocrystals prepared under identical conditions. In addition, Au–CuS hybrids could be used as templates to synthesize Au–CuInS2 and Au–Cu2 ZnSnS4 hybrid nanocrystals via subsequent reactions with In or Zn/Sn precursors at high temperature. These results provide insight into the critical parameters governing the growth of Au–copper sulfides hybrid nanostructures, which can be useful for the design of other noble metal–semiconductor hybrid nanostructures.